Interaction of magnetic fields with spinons in a fractionalized state - Yu Zhang; Hengdi Zhao; Tristan R. Cao; Rahul Nandkishore; Pedro Schlottmann; Lance De Long; Gang Cao (npj Quantum Materials)
Abstract The 4d-electron trimer lattice Ba₄Nb₁₋ₓRu₃₊ₓO₁₂ exhibits either a quantum spin liquid (QSL) or a heavy-fermion strange metal (HFSM) phase, depending on Nb content. In the QSL state, itinerant spinons act as effective heat carriers, enhancing thermal conductivity. Strikingly, applying a magnetic field up to 14 T causes an abrupt, up-to-5000% increase in heat capacity below 150 mK, disrupting the linear temperature dependence typical of both phases. Meanwhile, AC susceptibility and electrical resistivity remain nearly unchanged, while thermal conductivity drops by up to 40% below 4 K. These results suggest spinons, despite being charge-neutral, are highly sensitive to magnetic fields at low temperatures. We propose that the magnetic field could induce Anderson localization of spinons, creating emergent non-magnetic two-level systems responsible for the Schottky-like anomaly in heat capacity. These findings point to a previously unexplored regime of spinon dynamics, potentially governed by field-induced localization and distinct from conventional magnetic or transport signatures.